2013
DOI: 10.1037/a0032694
|View full text |Cite
|
Sign up to set email alerts
|

A pandemic of the poor: Social disadvantage and the U.S. HIV epidemic.

Abstract: The U.S. HIV epidemic has evolved over the past 30 years and is now concentrated in socially marginalized and disenfranchised communities. The health disparities in this epidemic are striking, with most HIV infections occurring in sexual minorities and communities of color. While widely recognized, the health disparities in HIV and AIDS are not often discussed. In this paper, we examine the factors underlying health disparities in the U.S. HIV epidemic. We first discuss the interlocking relationships between b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
290
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(303 citation statements)
references
References 139 publications
(159 reference statements)
11
290
1
1
Order By: Relevance
“…Second, within environments with physical inequality, we refer to variation in the salience of that physical inequity as situational inequality: for example, a floor plan that requires staff to walk past executive offices to arrive at their cubicles, or stadium or airplane seating that requires passing through the expensive seats to arrive at the less expensive ones. Indeed, previous research suggests that people's perceptions of their relative socioeconomic status are influenced by situational factors (15)(16)(17) and that the salience of inequality exerts an impact, as evidenced by poorer health outcomes in impoverished neighborhoods that border wealthier areas (18).…”
mentioning
confidence: 99%
“…Second, within environments with physical inequality, we refer to variation in the salience of that physical inequity as situational inequality: for example, a floor plan that requires staff to walk past executive offices to arrive at their cubicles, or stadium or airplane seating that requires passing through the expensive seats to arrive at the less expensive ones. Indeed, previous research suggests that people's perceptions of their relative socioeconomic status are influenced by situational factors (15)(16)(17) and that the salience of inequality exerts an impact, as evidenced by poorer health outcomes in impoverished neighborhoods that border wealthier areas (18).…”
mentioning
confidence: 99%
“…The course of HIV infection depends on various factors including the host, viral strain, treatment received and other environmental factors (1,2) . Treatment of concomitant infections is of primary importance in the delaying of disease progression in HIV-infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that simultaneous infections occurring with HIV infection can affect the HIV disease adversely (1) . Examples of these infections include tuberculosis, viral infections such as cytomegalovirus, and parasitic infections such as toxoplasmosis (2) .…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly disconcerting, because HIV has been termed a pandemic of the poor [41]. Similar to other health inequalities [42], risk and prevalence of HIV have also been associated with lower educational attainment and under-or unemployment-and are, thus, associated with lower Socioeconomic Status (SES), where SES is generally an aggregate measure of education, income, and occupational status.…”
Section: Stigma and Classmentioning
confidence: 99%